Pengaruh Variasi Waktu Pemeraman Terhadap Daya Dukung Tanah Lunak Gambut Kalimantan Selatan Distabilisasi Menggunakan Semen Portland - Akhmad Gazali; Robiatul Adawiyah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Stabilization is an attempt to improve the physical and mechanical properties of the soil so that it meets specific technical requirements. One method of stabilization is the addition of portland cement additives. This study aimed to compare the CBR values of soft soil of peat before and after stabilization with portland cement and to determine the effect of variations in ripening time on carrying capacity of soft soil peat. Soft peat soil used was taken from Handil Bakti Village, Alalak District, Barito Kuala District, South Kalimantan Province. Variations in the addition of cement levels used 5%, 10%, and 15%, while the variety of curing time starts from 7 days, 14 days and 21 days. In the results of the modified Proctor compaction test, the addition of cement levels in the soft soil of peat was shown to increase the maximum dry weight volume (γd) value continuously. While the value of optimum water content (ωopt) has decreased which is not too significant at each addition of cement content. For the value of the soft soil type of peat mixed with cement, the increase in weight compared with the original soil type weight. In CBR Laboratory testing using modified Proctor compaction at 15% cement content addition and 21 days curing time, the maximum CBR value of the Laboratory was 18.039%. The addition of Portland cement has been shown to increase the CBR value and the carrying capacity of the soil